Reduced egocentric bias when perspective-taking compared with working from rules. Issue 9 (September 2020) - Samuel, Steven; Frohnwieser, Anna; Lurz, Robert; Clayton, Nicola S
Previous research has suggested that adults are sometimes egocentric, erroneously attributing their current beliefs, perspectives, and opinions to others. Interestingly, this egocentricity is sometimes stronger when perspective-taking than when working from functionally identical but non-perspectival rules. Much of our knowledge of egocentric bias comes from Level 1 perspective-taking (e.g., judging whether something is seen) and judgements made about narrated characters or avatars rather than truly social stimuli such as another person in the same room. We tested whether adults would be egocentric on a Level 2 perspective-taking task (judging how something appears), in which they were instructed to indicate on a continuous colour scale the colour of an object as seen through a filter. In our first experiment, we manipulated the participants' knowledge of the object's true colour. We also asked participants to judge either what the filtered colour looked like to themselves or to another person present in the room. We found participants' judgements did not vary across conditions. In a second experiment, we instead manipulated how much participants knew about the object's colour when it was filtered. We found that participants were biased towards the true colour of the object when making judgements about targets they could not see relative to targets they could, but that this bias disappeared when the instruction was to imagine what the object looked like to another person. We interpret these findings as indicative of reduced egocentricity when considering other people's experiences of events relative to considering functionally identical but abstract rules.